Weepers : a novel - Mendelsund, Peter (Farrar, Straus and Giroux, 2025)
"Ed is a weeper. A professional weeper. He's a card-carrying member of an eccentric union hired to cry at funerals, wakes, services and burials. It's an odd job, but his services are sorely needed these days, as the town, the region, the country as a whole has become more or less numb. No one is able to summon a shred of human emotion whatsoever. Not anymore. (What'd be the point? The world's already gone to hell.) So there's always work for Ed and his colleagues. But all those cries can wear a man down, and the tears don't flow quite like they used to, even for a consummate pro like Ed."-- Amazon.com.